2020
DOI: 10.1186/s12889-020-09706-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of depression and resilience with fertility quality of life among patients presenting to the infertility centre for treatment in Karachi, Pakistan

Abstract: Background In Pakistan there is a dire need to explore the quality of life in infertile males and females and its undesirable psychological outcomes. This, study aimed to compare the quality of life (QoL) of males and females visiting an infertility centre for treatment and to assess its association with resilience, depression, and other socio-demographic factors. Methods An Analytical Cross-Sectional study was conducted amongst infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
0
15
0
2
Order By: Relevance
“…Meanwhile,In this study, social support had a positive effect on the core and treatment modules of fertility quality of life. The results of numerous studies ( Schaller et al, 2016 ; Namdar et al, 2017 ; Maroufizadeh et al, 2018 ; Bhamani et al, 2020 ) have shown that social support is an important factor in the quality of life of male infertility patients. With full support from family, society, hospital, and partner, male infertility patients will be more positive in coping with the treatment process and overcoming their internal pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile,In this study, social support had a positive effect on the core and treatment modules of fertility quality of life. The results of numerous studies ( Schaller et al, 2016 ; Namdar et al, 2017 ; Maroufizadeh et al, 2018 ; Bhamani et al, 2020 ) have shown that social support is an important factor in the quality of life of male infertility patients. With full support from family, society, hospital, and partner, male infertility patients will be more positive in coping with the treatment process and overcoming their internal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Further, infertile patients often perceive themselves as craving support from social network members ( High and Steuber, 2014 ). Most studies have shown that social support is an important factor affecting the quality of life of male infertility patients ( Schaller et al, 2016 ; Namdar et al, 2017 ; Maroufizadeh et al, 2018 ; Bhamani et al, 2020 ). With full support from family, society, hospital, and partners, male infertility patients will be more active in the treatment process and overcome their inner pain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large cross-sectional study on 7352 women with infertility has shown that 56% of women with infertility reported significant symptoms of depression, and 76% of women reported significant symptoms of anxiety (Pasch et al, 2016). In turn, anxiety and depression not only lead to the failure of infertility treatment (Crawford et al, 2017;Rich & Domar, 2016) but also reduce their quality of life (Bhamani et al, 2020;Chaudhari et al, 2018), affect pregnancy outcome (Hosaka et al, 2002;Purewal et al, 2017)s, and even become a factor of suicide in infertile women (Shani et al, 2016). Thus, effective therapeutic interventions for infertile female patients are urgently required to address their physical and psychosocial problems.…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation is applied to the woman by her family and the woman can be threatened with divorce. At the end of this process, mental disorders and suicide can be seen more among women as compared with infertile men (Bhamani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%